COPYRIGHT PROTECTION FOR NON-FUNGIBLE TOKENS AS DIGITAL ARTWORKS - Halim, Chandera; Sukmaningrum, Anastasia Angger (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The current technological developments have provided convenience for society in accessing the internet, which can be utilized in various fields, one of which is the economy. In economic activities through digital media, the term "digital economy" is used. Digital economic activities cannot be separated from copyright objects that are traded as goods. Considering that examining copyright issues ultimately leads to the concept of law itself, especially regarding efforts to protect the results of two-dimensional art in the form of Non-Fungible Tokens (NFTs), it is important to address this matter. The buying and selling of NFT art in digital media brings fresh opportunities for artists. However, it also creates problems for some parties in protecting their creations from harmful actions. Therefore, this research aims to understand the legal protection for creators of two-dimensional digital artworks, to facilitate economic activities, and to identify the appropriate legal actions for creators in the event of copyright infringement in digital media. In this research, the author employs a normative research method, focusing on literature and secondary data through a juridical-normative approach that is descriptive and analytical in nature. The study reviews and analyzes regulations related to the core issues at hand. The findings of this research clearly show that, in fact, Indonesian Law Number 28 of 2014 on Copyright and Law Number 19 of 2016 on Amendments to Law Number 11 of 2008 on Electronic Information and Transactions do not comprehensively regulate two-dimensional digital artworks. To address emerging issues, creators can take legal action in the form of filing a compensation lawsuit in commercial courts, submitting criminal reports, or filing a report to the Directorate General of Intellectual Property to request the removal of content and/or access rights if copyright infringement is suspected in digital media.